A new species of Cornutalis Sakakibara (Membracidae: Smiliinae: Acutalini) from Colombia - Flórez-V, Camilo (Zootaxa, 2017)
The genus Cornutalis Sakakibara currently includes two valid species, Cornutalis cauca Sakakibara, 1997 (from Colombia) and C. valida Sakakibara, 1997 (from Ecuador). Herein, a new species, Cornutalis andinum sp. n., is described from the highlands in Colombia; additionally, a host plant is recorded for the first time for the genus. Also, a distribution map, a key to the species, and observations on the location and preservation state of type-specimens are included.